Performance measurement of UCITS investment funds in Croatia - Marko Curkovic; Jaksa Kristo (UTMS Journal of Economics, 2017)
UCITS investment funds represent an important investment opportunity for retail, as well for institutional investors in the European Union. The aim of this paper is to analyse the performance of the UCITS investment funds in Croatia and to detect relatively homogeneous groups among the UCITS funds based on its performance. The analysis includes 55 UCITS, in the period from the beginning of 2011 until the end of 2014, and it is conducted on daily data of share prices, available from Bloomberg terminal. Analysis is performed separately within the groups of different investment fund by investment strategy. The research methodology is based on the calculation of various indicators of absolute and relative risk-adjusted performance and riskiness of the funds. In general, based on analysis of performance measures, it can be concluded that funds with higher values of net assets were more successful compared to the funds with below-average asset values. Also, funds with below-average values of net assets were more volatile. At the same time, funds run by foreign own management companies were more successful by the absolute performance measures, compared to funds run by management companies with domestic ownership. On the other hand, those funds were more volatile, as well.
Keywords: G23; 330; absolute risk-adjusted performance; relative risk-adjusted performance; Sharpe ratio; Information ratio